Non-Abelian Sugawara construction and the q-deformed N=2 superconformal algebra - Batista, E.; Gomes, J. F.; Lautenschleguer, I. J. (Iop Publishing Ltd, 1996)
The construction of a q-deformed N = 2 superconformal algebra is proposed in terms of level-1 currents of the U-q(<(su)over cap>(2)) quantum affine Lie algebra and a single real Fermi field. In particular, it suggests the expression for the q-deformed energy-momentum tensor in the Sugawara form. Its constituents generate two isomorphic quadratic algebraic structures. The generalization to U-q(<(su)over cap>(N + 1)) is also proposed.